Caracterización del acceso al empleo y gastos familiares en pobladores del pueblo joven Vargas Guerra ciudad de Iquitos año 2023 - Mantari Garcia, Veronica Luz (2023)
Access to employment represented in the generation of resources for families linked to the characterization of expenses is an aspect that is studied in general, but it is not focused by geographical sectors with the purpose of mapping how this aspect is presented or perceived. of the economic and social development of the population; The present study determined how access to employment and family expenses are presented in residents of the young town Vargas Guerra, city of Iquitos, year 2023, developing a non-experimental, cross-sectional and observational quantitative research, with a population made up of 75 individuals from the area. , the work identified that 33% carried out a paid activity in the last 12 months, that 57% are in search of employment, that 9% have a formal and permanent job, that 80% work independently, that the 76% consider it difficult to access a job and only 9% receive a salary and benefits according to law, likewise that the majority of residents do not meet their food needs 88%, health 60%, educational 49% and recreational 91%, that 75% consider food expenses as more relevant and that 65% consider that food expenses are higher than 12 months ago, concluding that access to employment and family expenses present significant characteristics for both variables.